2020
DOI: 10.1051/ro/2019038
|View full text |Cite
|
Sign up to set email alerts
|

Decision policies on players’ different risk combination under supplier encroachment

Abstract: Literature concerning about the supply chain management problem is usually based on perfect rationality. However, risk preferences have been proved to be an important role which influences managers' decisions significantly. This paper investigates a risk combination problem under supplier encroachment with different risk preferences players. Assuming that the supply chain players may be risk-averse, risk-neutral and risk-taking, we build a Stackelberg game model to explore the optimal decisions and the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In four models, we do not facilitate product differentiation or price discrimination. 10 This is to reflect the fact that suppliers are concerned about reputational backlash when customers discover different pricing schemes for different channels, as is noted in Cattani, et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In four models, we do not facilitate product differentiation or price discrimination. 10 This is to reflect the fact that suppliers are concerned about reputational backlash when customers discover different pricing schemes for different channels, as is noted in Cattani, et al…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers [1,[7][8][9][10] have addressed supplier encroachment on the assumption that suppliers sell products through a supplier-owned direct channel, thus ignoring the role played by the online platform and its impact on the traditional retailer, online pricing strategies and profits. Moreover, it has long been recognised that supplier encroachment has strategic consequences on sustainable operations.…”
Section: Introductionmentioning
confidence: 99%
“…Our work also relates to suppliers' encroachment in a supply chain (see, e.g., Liu and Zhang, 2006;Li et al, 2014Li et al, , 2015Chen, Ping et al, 2020;Ma, Junhai and Hong, Yalan, 2021). Arya et al (2007) showed that encroachment is beneficial to the retailer when no synergies are admitted by the supplier.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Recent studies considering encroachment under information asymmetry in a single selling period include Li et al [27,28], Huang et al [22], Yang et al [49], and Zhang et al [52], and recent studies considering encroachment under information symmetry in two-period settings include Xiong et al [45] and Yan et al [48]. More recently, Chen et al [12] studied a supplier encroachment problem in a supply chain in which the supplier and the retailer exhibit different risk attitudes and showed that in the supplier-led Stackelberg game, the combination of the supply chain members with preferred risk attitudes does not necessarily benefit the supply chain. Liu et al [31] considered a supply chain with one supplier and multiple retailers and showed that supplier encroachment hurts the supplier when the number of retailers is sufficiently large.…”
Section: Literature Reviewmentioning
confidence: 99%